Analysis of Public Knowledge Regarding Preparedness in Facing Earthquake Disasters: A Literature Review - Farida Nayla Kholillah Ruswan; Syarif, Ahmad (Journal of Diverse Medical Research : Medicosphere, 2024)
Background: Earthquakes are one of the natural disasters that often occur in various countries. In 2023, there were 10,789 earthquakes in Indonesia with 54,652 fatalities. Method: in the form of a literature review by collecting information taken from several journals in the form of primary data. The data obtained came from the PubMed, NCBI, Google Scholar, Mendeley, ResearchGate, and Scopus databases for the last 5 years based on keywords. Purpose: This article aims to improve community preparedness for earthquake disasters. Results: Educational counseling and simulations carried out to foster public understanding of disaster preparedness are the right steps to build public awareness of the importance of disaster preparedness in accordance with established guidelines. Preparedness as stipulated in Law No. 24/2007 concerning Disaster Management is defined as a series of activities carried out to anticipate disasters through organizing with appropriate and efficient steps. Conclusion: Increasing community capacity through appropriate health promotion will have an impact on the level of local community participation in understanding the importance of disaster preparedness, especially earthquakes in the area. Keywords: Disaster, Earthquake, Preparedness, Counseling